Evaluation of Anti-proliferative Effects of Barringtonia racemosa and Gallic Acid on Caco-2 Cells - Ho, Ivan Y. M. (Sci Rep, 2020)
Barringtonia racemosa leaf water extract (BLE) had been shown to have high gallic acid (GA) content and BLE has been postulated to have anti-proliferative effects towards colorectal cancer. This study aims to further investigate the mechanism underlying the anti-proliferative effect of BLE in Caco-2 cells and to determine if GA is responsible for the observed effects. Both BLE and GA inhibited Caco-2 cells in a dose-dependent manner. Cells exposed to IC(50) concentration of BLE and GA showed reduced antioxidant activities. GA-treated Caco-2 cells experienced higher oxidative stress compared to cells treated with BLE. Both BLE and GA significantly up-regulated the expression of SLC2A1. BLE but not GA, significantly down-regulated the expression of ADH4. Meanwhile, GA but not BLE, significantly up-regulated AKRIB10 and GLO1 but significantly down-regulated HAGH. Alterations in gene expression were coupled with changes in extracellular glucose and pyruvate levels. While BLE decreased intracellular pyruvate, GA did the opposite. Both intracellular and extracellular D-lactate were not affected by either BLE or GA. GA showed more pronounced effects on apoptosis while BLE irreversibly reduced cell percentage in the G0/G1 phase. In conclusion, this study demonstrates the multiple-actions of BLE against Caco-2 cells, potentially involving various polyphenolic compounds, including GA.